Hypersonic flow past nose cones of different geometries: a comparative study. (August 2018) - Narayan, Ashish; Narayanan, S; Kumar, Rakesh
The present work provides a detailed comparative study of the hypersonic flow past spherically blunted and parabolic nose cones at a Mach number of 5.8, numerically. The main focus of the paper is to determine the geometry and parameters of the nose cones that provide minimum aerodynamic drag and heating. Studies on spherically blunted and parabolic nose cones are performed for different fineness ratios at zero angle of attack. It is observed that for fineness ratio <1.2, blunted cones provide minimum drag, whereas at higher values of fineness ratios >1.2, parabolic nose cones provide superior drag reduction. Detailed comparison of the flow/shock features in the vicinity of the blunted and parabolic nose cones for different fineness ratios is also shown in order to determine its influence on aerodynamic drag. An empirical correlation developed for the total drag coefficient based on regression analysis for a parabolic nose cone reveals that it is mainly a function of the maximum pressure coefficient and fineness ratio. In general, the present study reveals that parabolic nose cones at higher fineness ratios are preferred over spherically blunted ones for achieving higher drag reductions and lower heating in hypervelocity vehicles.